Product lifecycle management : geometric variations - Giordano, Max.; Mathieu, Luc, 1954-; d (London : ISTE ; Hoboken, NJ : Wiley, 2010)
This book gives a comprehensive view of the most recent major international research in the field of tolerancing, and is an excellent resource for anyone interested in Computer Aided Tolerating. It is organized into 4 parts. Part 1 focuses on the more general problems of tolerance analysis and synthesis, for tolerancing in mechanical design and manufacturing processes. Part 2 specifically highlights the simulation of assembly with defects, and the influence of tolerances on the quality of the assembly. Part 3 deals with measurement aspects, and quality control throughout the life cycle.
Pt. 1. Tolerance analysis and synthesis -- pt. 2. Simulation of assemblies -- pt. 3. Measurement -- pt. 4. Tolerancing in the PLM.
Title from PDF title page (viewed on Feb. 20, 2013).
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Product life cycle -- Congresses; Tolerance (Engineering) -- Congresses; Geometry, Descriptive -- Congresses; Produits commerciaux -- Cycle de vie; v; v; TECHNOLOGY & ENGINEERING -- Quality Control; Geometry, Descriptive; Product life cycle; Tolerance (Engineering); Conference papers and proceedings